Can pre‐eclampsia explain higher cesarean rates in the different groups of Robson's classification?. Issue 3 (28th September 2020) - Sanchez, Mariana P.; Guida, Jose P.; Simões, Marcela; Marangoni‐Junior, Marcos; Cralcev, Christopher; Santos, Juliana C.; Dias, Tabata Z.; Luz, Adriana G.; Costa, Maria L.
Abstract: Objective: To evaluate the impact of pre‐eclampsia on cesarean delivery by using the Robson classification. Methods: A retrospective cross‐sectional study including all women who delivered in a referral maternity hospital in southeast Brazil from January 2017 to February 2018. Women were classified into 1 of 10 Robson groups and then further subdivided into pre‐eclampsia (PE) and non‐PE (NPE) groups. Frequency of cesarean was determined for each group and compared by using χ 2 and prevalence ratio. Results: Overall, 3102 women were included, of whom 1578 (50.9%) delivered by cesarean. Classification in Robson group 5 was the most frequent among all women (n=727, 23.4%). In the PE group (n=258, 8.3%), group 10 was the most frequent classification (n=120, 46.5%); in NPE, Robson group 5 was the most frequency (n=682, 24.0%). Pre‐eclampsia was associated with a higher occurrence of cesarean (77.5% vs 48.4%; prevalence ratio, 2.29; 95% confidence interval, 1.82–2.82), owing to higher rates in Robson groups 1, 5, and 10. Conclusion: Pre‐eclampsia was associated with a higher occurrence of cesarean delivery in some Robson groups. Robson classification may be used to evaluate the impact of specific conditions at a facility level to help plan future interventions to optimize the use of cesarean. Synopsis: Robson classification is a tool to assess cesarean delivery that can be used to compare rates between women with specific conditions such as pre‐eclampsia.